Health and socio-demographic implications of the Covid-19 second pandemic wave in Israel, compared with the first wave - Daphna Birenbaum-Carmeli; Judith Chassida (BMC, 2021)
Abstract Background Israel's containment of the first wave of Covid-19 was relatively successful. Soon afterwards, however, in the summer months, a harsher pandemic wave developed, resulting in many more seriously ill and dead Israelis. Israel was the world's first country to impose a second general lockdown. The present study outlines the early months of Israel's second pandemic wave, until the imposition of the second general lockdown, and their impact on various communities. The investigation is conducted in conjunction with five sociodemographic variables: population density, socioeconomic status, rate of elderly population, minority status (Jewish / Arab identity) and religiosity (Ultra-Orthodox vs. other Jewish communities). Methods The analysis is based on a cross sectional study of morbidity rates, investigated on a residential community basis. Following the descriptive statistics, we move on to present a multivariate analysis to explore associations between the five aforementioned sociodemographic variables and Covid-19 morbidity in Israel in the early second pandemic wave vs. the first Covid-19 outbreak. Results Both the descriptive statistics and regressions show morbidity rates to be significantly and positively associated with communities' population density and significantly and negatively associated with socioeconomic status (SES) and the size of elderly population. These results differ from Wave I morbidity, which was not significantly associated with SES. Another difference vis-a-vis Wave I is the rise of morbidity in Arab communities that led to the disappearance of the previously observed significant negative association of morbidity with minority (Arab) status. Exceptional morbidity was found in Ultra-Orthodox Jewish communities. Conclusion The second wave of Covid-19 in Israel has profoundly affected marginalized communities characterized by high residential density, low SES and minority status. Other marginalized and disempowered communities have also been badly hit. While acknowledging the potential contribution of various possible causes, we highlight the policy response of Israel's government during the early weeks of the second Covid-19 outbreak, suggesting that the severe second wave might possibly be associated with belated, undecided government response during this period.